STRATEGI PROMOSI OBJEK WISATA AIR TERJUN MASPAIT DUSUN TAENO NEGERI RUMAHTIGA BERBASIS ANDROID - Gilbert Alvin Rumalatu; Eka Adhitya Dharmawan (Jurnal Administrasi Terapan, 2025)
This study examines the promotional strategy for the Maspait waterfall tourist attraction in Taeno Hamlet, Negeri Rumahtiga by utilizing an Android -based application to increase visibility, interaction and visits. This research approach uses a case study method with quantitative data collection through visitor surveys and qualitative analysis of interviews with tourist attraction managers. The results of the study revealed that the use of interactive map features, complete tourist attraction information, visitor reviews and event notification features on the Android application significantly increased tourist understanding and interest in visiting tourist attractions. An example of a simple Android program has also been developed to demonstrate the implementation of these features. Keywords: Tourism Promotion, Android Application, Digital Marketing